ANALISIS RASIO SOLVABILITAS DAN AKTIVITAS UNTUK MENILAI KINERJA KEUANGAN PADA PT. ANEKA GAS INDUSTRI - Ikhsan Abdullah; Lestari . (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
Financial statement analysis is a process that full consideration in order to help evaluate the financial position and results of operations of the company in the present and the past, with the aim to determine the elimination and the most likely prediction about the condition and performance of the company in the future. This study aimed to see whether the performance of the company is in good condition or not then be compared with the average standard of the industry. Analyzer used in PT. Aneka Gas Industri Medan is the solvency ratio, the debt to asset ratio (DAR) and the debt-to-equity ratio (DER) and the ratio of activity, namely the total asset turnover (TATO). The solvency ratio indicates the extent to which the company is capitalized with debt. Activity ratio indicates a company's ability to carry out daily activities. In this research using descriptive analysis techniques and sources of secondary data by using documentation and interviews. Based on the results of this study concluded that the views of the DAR, DER, and TATO shows the company's debt is still quite high due to the considerable assets to use debt financing, the imbalance of debt rise with the increase in owner's equity, and the lack of effective companies using owned assets to generate sales maximum. So that the resulting financial performance at PT. Aneka Gas Industri Medan overall assessed poorly and yet meet the standards of the industry average.